Does the Single Draft of COC in the South China Sea Matters? - Haryanto, Agus; Darmawan, Arief Bakhtiar (Intermestic: Journal of International Studies, 2020)
This paper attempts to elaborate on the impact of the Single Draft of CoC in resolving the South China Sea (SCS) dispute. This paper uses the concept of International Dispute Settlement Procedures (IDSPs), where the parties try to resolve problems based on international law. This paper argues that countries in the region have been trying to have CoC mechanisms since the 1990s. Although in 2018, the ASEAN countries and China agreed on a Single Draft of CoC in the SCS, however the settlement of the SCS dispute is far from over. The CoC Single Draft is only a collection of ASEAN and China proposals. The Single Draft weaknesses in terms of legal status are they do not clearly state the obligations of each country to add or withdraw their respective proposals.